Antifouling poly(vinylidene fluoride) hollow fiber membrane with hydrophilic surfaces by ultrasonic wave‐assisted graft polymerization. (5th December 2018) - Qi, Yating; Shao, Huiju; Luo, Dajun; Xiang, Li; Luo, Jiyong; Tian, Qin; Qin, Shuhao
Abstract : Acrylic acid (AA)‐grafted poly(vinylidene fluoride) (PVDF) hollow fiber membrane was obtained by ultrasonic wave‐assisted graft polymerization. The grafting density (GD) of AA on the PVDF membrane surface could be controlled by altering the reaction conditions, such as ultrasonic time, ultrasonic power, monomer concentration and initiator concentration. The attenuated total reflectant Fourier transform infrared spectra (FITR‐ATR) and X‐ray photoelectron spectroscopy were used to investigate the chemical composition of modified membranes. The changes of surface morphology and roughness were characterized by field emission scanning electron microscope and atomic force microscopy. Results show that AA was successfully grafted on the membrane surface. With increasing GD, the static water contact angle was decreased from 95.7 to 41.4°, indicating that hydrophilicity of modified membrane was significantly enhanced. Pure water flux before and after bovine serum albumin (BSA) contamination was measured. The modified membrane with the GD of 0.76 mg/cm 2 has the highest water flux as high as 350 L/m 2 ·h. When compared with the pristine membrane(M0), the flux recovered ratio was improved from 52.75 to 96.29% at the GD 2.76 mg/cm 2 (M3), which suggested the protein fouling could be effectively prevented for the modified membrane. POLYM. ENG. SCI., 2018. © 2018 Society of Plastics Engineers POLYM. ENG. SCI., 59:E446–E454, 2019. © 2018 Society of Plastics Engineers